To solve the quadratic equation \( x^2 - 16x + 64 = 0 \) using the perfect square trinomial pattern, we can first recognize that the expression on the left side can be written as a square.
The equation can be factored as follows:
\[ x^2 - 16x + 64 = (x - 8)^2 \]
Therefore, we can rewrite the equation as:
\[ (x - 8)^2 = 0 \]
Next, we take the square root of both sides:
\[ x - 8 = 0 \]
Now, we solve for \( x \):
\[ x = 8 \]
Thus, the solution to the equation \( x^2 - 16x + 64 = 0 \) is
\[ \boxed{8} \]